1997
DOI: 10.1063/1.473428
|View full text |Cite
|
Sign up to set email alerts
|

A first-passage algorithm for the hydrodynamic friction and diffusion-limited reaction rate of macromolecules

Abstract: A first-passage scheme for determination of overall rate constants for non-diffusion-limited suspensions J. Chem. Phys. 116, 3128 (2002) Many important properties of a macromolecule can be expressed in terms of averages over the trajectories of diffusing particles that begin in the medium surrounding the molecule and terminate at its surface. These properties include its translational hydrodynamic friction coefficient and the Smoluchowski rate constant for diffusion-limited reactions. In this paper we introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…However, as shown by Veshchunov (2010), in the continuum limit, analysis via the steady-state flux approach (the diffusion regime) and of dilute, homogenously distributed systems (the kinetic regime) lead to matching functional forms of the continuum regime collision kernel. For this reason, mean first passage time calculations and related Brownian Dynamics algorithms can and have been successfully employed to determine diffusion-limited reaction rates in the continuum regime (Klein 1952;Northrup et al 1984Northrup et al , 1986Douglas et al 1994;Given et al 1997) and are employed here for rate determination in the continuum, transition, and free molecular regimes.…”
Section: Simulation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as shown by Veshchunov (2010), in the continuum limit, analysis via the steady-state flux approach (the diffusion regime) and of dilute, homogenously distributed systems (the kinetic regime) lead to matching functional forms of the continuum regime collision kernel. For this reason, mean first passage time calculations and related Brownian Dynamics algorithms can and have been successfully employed to determine diffusion-limited reaction rates in the continuum regime (Klein 1952;Northrup et al 1984Northrup et al , 1986Douglas et al 1994;Given et al 1997) and are employed here for rate determination in the continuum, transition, and free molecular regimes.…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…Accurate calculation of collision rates thus requires accurate calculation of β. When the radius of at least one object is large relative to the mean persistence distance of the colliding entities (Rader 1985), the continuum approximation is satisfied and Smoluchowski's β applies (Chandrasekhar 1943;Given et al 1997):…”
Section: Introductionmentioning
confidence: 99%
“…This problem has no analytic solution, and has long been regarded as a benchmark in the electrostatic theory [3]. Different computational methods were used to solve it: boundary element [21,23,4], finite-difference [22], and stochastic algorithms [24,9,7] as well. The results (in units of 4π 0 ) and their published errors (in different senses) are given in Table 1.…”
Section: Computational Results For the Unit Cubementioning
confidence: 99%
“…Recently, it has been found that in computing the capacitance, the diffusion limited reaction rate, and other related properties of arbitrary shaped bodies, stochastic simulation algorithms can be competitive with boundary element and other conventional deterministic computational methods [7]. In many cases, simple Brownian dynamics simulations can be substantially refined, making it possible to use the walk on spheres (WOS) [8] and the Green's function first passage (GFFP) Monte Carlo methods [9]. Elimination of the WOS bias due to the boundary with GFFP, the simulation-tabulation technique [10], and last passage variants of these Monte Carlo algorithms [11] further extend the capabilities of stochastic computational methods when applied to electrostatics problems.…”
Section: Introductionmentioning
confidence: 99%
“…The 'walk on spheres' (WOS) method (described in [20]) is based on such an approach. The Green's function first passage (GFFP) Monte Carlo method [9] is the natural extension of WOS [12]. The simulation-tabulation technique [14], and last passage variants of the GFFP algorithm [10], further extended the capabilities of stochastic computational methods when applied to solving electrostatics and similar problems.…”
mentioning
confidence: 99%